An accurate and reproducible method for simultaneous determination of four flavonoids in EtOAc extracts from Sophora flavescens Ait. in rat plasma based on UHPLC Q‐Exactive Mass spectrometry: Application to a pharmacokinetics study. (21st December 2018) - Chen, Lei; Zhao, Linlin; Cai, Wei; Shao, Jing; Huang, Xiaobin; Liu, Yi
Abstract: In previous studies, it was revealed that ethyl acetate (EtOAc) extracts from Sophora flavescens Ait. improved glucose tolerance, reduced hyperglycemia, and restored insulin levels in diabetic patients. The aim of this study was to develop an accurate and sensitive UHPLC–MS method for simultaneous determination of flavonoids in EtOAc extracts of Kushen in rat plasma. Ethyl acetate–acetonitrile (2:1) was selected as the solvent to extract the four flavonoids from rat plasma. A BEH C18 column (2.1 mm × 100 mm, 1.7 μm) with a C18 guard cartridge was chosen as the separation plant using a gradient elution with acetonitrile (solvent A) and 0.1% formic acid (solvent B) in water. For all four analytes, the method showed good linearity ( r 2 > 0.991) in 1–500 ng/mL. The inter‐ and intra‐day accuracy ranged from −13.78 to 7.19%, and the precision (RSD) was <8.75%. Recoveries of all four flavonoids ranged from 85.9 to 101.3%. According to the results of multitarget pharmacokinetic studies, four active flavonoids in EtOAc extracts from Kushen have similar absorption kinetics but very different metabolic kinetics, and a double peak phenomenon was observed in the concentration–time curve of norkurarinone, which is different from the previous study. In conclusion, detection and multitarget pharmacokinetic studies successfully determined active flavonoids after oral administration of EtOAc extracts from Kushen by an efficient, sensitive and selective UHPLC–MS method, and the results may provide a foundation for future studies of Kushen.